2018
DOI: 10.1177/0143034318777781
|View full text |Cite
|
Sign up to set email alerts
|

The examination of authoritarian parenting styles, specific forms of peer-victimization, and reactive aggression in Hong Kong Youth

Abstract: This study utilized a hierarchical regression model to explore the relationship between reactive aggression, forms of peer victimization, and authoritarian parenting styles. Participants included 1,021 Hong Kong youth and their parents ( N = 1,021), drawn from ten primary schools throughout the municipality. Children completed the Reactive and Proactive Aggression Questionnaire and the Multidimensional Peer Victimization Scale, while parents completed the Parental Styles Dimensions Questionnaire. Results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 74 publications
2
4
0
5
Order By: Relevance
“…Parents higher in authoritarian parenting are more likely to restrict children's exploration and problem‐solving, and instead, encourage children's dependence on their parents’ guidance (Friedson, 2016). Because punitive behaviors and hostility are likely to be related to children's anxiety, fear, and anger, it is not surprising that children of authoritarian parents tend to have low self‐worth and negative attitudes toward the world (Chan et al, 2018; Shaw & Starr, 2019). This, in turn, may contribute to children's development of internalizing problems (Akhter et al, 2011; Fuentes et al, 2015).…”
Section: Marital Conflict and Child Internalizing Problems: Direct An...mentioning
confidence: 99%
“…Parents higher in authoritarian parenting are more likely to restrict children's exploration and problem‐solving, and instead, encourage children's dependence on their parents’ guidance (Friedson, 2016). Because punitive behaviors and hostility are likely to be related to children's anxiety, fear, and anger, it is not surprising that children of authoritarian parents tend to have low self‐worth and negative attitudes toward the world (Chan et al, 2018; Shaw & Starr, 2019). This, in turn, may contribute to children's development of internalizing problems (Akhter et al, 2011; Fuentes et al, 2015).…”
Section: Marital Conflict and Child Internalizing Problems: Direct An...mentioning
confidence: 99%
“…Consistent with this view, empirical literature has shown that adolescents subjected to peer rejection and provocations tend to perceive peers' intentions as hostile, leading to an increased likelihood of reactive rather than proactive aggression (Camodeca et al, 2002 ; Card and Little, 2006 ; Fite et al, 2012 ; Brown et al, 2016 ). In line with these studies, Chan et al ( 2018 ) found that that verbal victimization by peers significantly contributes more to adolescent reactive aggression than proactive aggression in a sample of more than 1,000 Hong Kong youth. Considering this evidence, we expect that perceived discrimination is more strongly related to adolescent reactive aggression than proactive aggression.…”
Section: Introductionmentioning
confidence: 80%
“…지금까지 수행된 초등학생의 반응적 공격성과 관련한 연구들 은 부모로부터의 학대경험, 또래괴롭힘, 적대적 귀인편향 등이 중 요한 예측 요인임을 보고하였다 (Chan et al, 2018;Gao et al, 2015;Kwon & Park, 2015). 그중에서도 초등 고학년인 아동기 중반은 또래와 보내는 시간이 늘어나면서 또래 집단의 영향이 증 가하는 시기라는 점에서, 중요한 타인인 또래와의 긍정적 관계 를 형성하지 못할 경우 좌절을 경험하게 되며 이는 반응적 공격 성에 영향을 미치는 주요 요인으로 작용할 것을 예측해볼 수 있 다 (Jung, 2015).…”
unclassified
“…따라서 또래 관 계의 중요성이 증가하는 아동기에 또래괴롭힘이라는 적대적인 사 건을 많이 경험한 아동은 상대방의 의도가 불분명한 상황에서 조 차도 자신을 위협한다고 생각하여 이에 보복하는 반응적 공격성 을 더 많이 보일 수 있다 (Card & Little, 2006). 실제로 선행연구 들 (Camodeca & Goossens, 2005;Chan et al, 2018) (Dodge et al, 1990).…”
unclassified
See 1 more Smart Citation